Masalah Belajar yang Dialami Oleh Peserta Didik dalam KBM pada Kelas 5 Di SD Negeri 03 Probur Utara - Gaudensius S. Yenifana; Yerimia S. Wabang; Pilmon Karmaley; Saaltiel Mohar (Jurnal Kajian dan Penelitian Umum, 2025)
Learning problems are conditions that hinder students from achieving specified competencies. This problem can be caused by internal factors such as cognitive, affective, physical, motivational and external factors such as environmental or social weaknesses. Learning difficulties are not only experienced by students with below average abilities, but also students with above average abilities. Non-intellectual factors such as motivation, physical condition, and a learning environment that is not conducive to learning are often the main causes. Qualitative research methods were used to identify student learning problems during Field Experience Practice (PPL). Data collection was carried out through interviews with teachers and direct observation in the field. Interviews are used to obtain information about the preparation of teaching modules, mastery of material, and classroom management. Observation techniques provide a comprehensive picture of the practical problems faced by students during PPL. This research found that student learning problems are influenced by various interrelated factors, both from within the student and from the external environment. Therefore, a holistic approach is needed to overcome learning problems, including providing emotional, physical and environmental support that is conducive to optimal learning.